Neurological outcomes and cure rates of embolization of brain arteriovenous malformations with n-butyl cyanoacrylate or Onyx: a meta-analysis. (24th December 2014) - Elsenousi, Abdussalam; Aletich, Victor A; Alaraj, Ali
Abstract : Background: In the past decade, preoperative endovascular embolization of cerebral arteriovenous malformations (AVMs) became an essential tool in the treatment of these entities. With the current expansion of technology and wide incorporation of new devices, the indications for the use of endovascular embolization have expanded to include embolization for cure. This has been facilitated by the wide use of the new liquid embolic agents (ethylene-vinyl alcohol co-polymer (EVOH)) in addition to n-butyl cyanoacrylate (NBCA). The aim of this study was to review the current published literature for these two agents and report on permanent neurological injuries and cure rate. Methods: Published literature citing embolization results for AVMs using liquid embolic agents was reviewed. Papers reporting on permanent complication rates and complete angiographic cure were reviewed. A meta-analysis was performed based on these two variables for the two embolic agents. Results: 103 studies met the selection criteria. Poor neurological outcomes for NBCA and EVOH were 5.2% and 6.8%, respectively (OR 1.4; p=0.56). AVM complete obliteration rate was seen in 13.7% in the NBCA group and in 24% in the EVOH group (OR 1.9). This OR decreased to 1.35 in the subgroup analysis for patients treated after the year 2000. Conclusions: NBCA continues to have a trend towards lower permanent complication rates, but EVOH had higher angiographic cure rates. The recent literature has demonstrated an increase in the cure rate of AVMs with endovascular embolization techniques yet with a possible increase in permanent neurological deficits and mortality.